Defect-rich molybdenum-doped fuel cell oxygen reduction catalyst and preparation method thereof
By using organic framework compounds and ammonium salt pyrolysis technology in fuel cell oxygen reduction catalysts, defect-rich molybdenum single-atom doping catalysts are prepared, which solves the problems of high and unstable existing catalysts and achieves high efficiency and low cost The oxygen reduction reaction is environmentally friendly and pollution-free.
Patent Information
- Application Number
- CN202411527186.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2024-12-31
AI Technical Summary
Existing fuel cell oxygen reduction reaction catalysts are costly and unstable, making it difficult to meet the needs of large-scale industrial production, especially when exhibiting instability at high potentials, limiting their application.
Using organic framework compounds as nitrogen-doped carbon precursors, uniformly disperse trace amounts of precious metal salts and molybdenum sources, through hydrothermal synthesis and high-temperature carbonization, combined with ammonium salt pyrolysis, defect-rich molybdenum single-atom doping catalysts, molybdenum and precious metals are prepared. Dispersed on the carbon substrate in a single atomic state, forming an efficient and low-cost oxygen reduction catalyst.
The kinetics of the oxygen reduction reaction are improved, the load of precious metals is reduced, the production cost is reduced, and the active sites of the catalyst are increased through ammonium salt pyrolysis, which improves catalytic activity. At the same time, the process is simple, environmentally friendly and pollution-free.
Smart Images

Figure CN119230854A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of oxygen reduction, and in particular to a fuel cell oxygen reduction catalyst and a preparation method thereof. Background Art
[0002] With the gradual depletion of fossil energy and the significant environmental problems caused by the over-exploitation of these resources, the search for alternative clean energy has become one of the most concerned issues in the current energy and chemical industry. As a highly efficient energy conversion and storage device, the development of fuel cells is imperative. However, the slow kinetics of the cathode oxygen reduction reaction greatly limits its application, and there is an urgent need to develop economical and efficient oxygen reduction reaction catalysts.
[0003] At present, the performance of platinum group noble metal catalysts represented by platinum, iridium, ruthenium, etc. is the most ideal. However, due to their extremely high application cost and instability under high potential, direct application is difficult to meet the requirements of large-scale industrial production. Therefore, people began to shift their attention to non-noble metal catalysts with low cost and high stability under alkaline conditions. Low-platinum catalysts are modified with non-noble metals to prepare economical catalysts with excellent performance.
[0004] Patent document CN111545208A discloses a cobalt-nickel bimetallic catalyst and its preparation method, which uses biological small molecules as nitrogen sources to prepare porous carbon, and in-situ loads or coats metal organic framework complexes and performs high-temperature pyrolysis to prepare heteroatom-doped cobalt-nickel bimetallic catalysts, but its half-wave potential is 0.83 V. Therefore, the development of efficient and low-cost catalysts is currently a hot topic in research and development. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention proposes a defect-rich molybdenum-doped fuel cell oxygen reduction catalyst and a preparation method thereof. An organic framework compound is used as a nitrogen-doped carbon precursor, a trace amount of precious metal salt and a molybdenum source are uniformly dispersed in the precursor solution, hydrothermally synthesized, and an appropriate amount of ammonium salt is placed in the air inlet of a tubular furnace to perform high-temperature carbonization on the precursor to prepare a defect-rich molybdenum single atom-doped catalyst.
[0006] In order to achieve the above objectives, on the one hand, the present invention provides a defect-rich molybdenum-doped fuel cell oxygen reduction catalyst, which comprises a nitrogen-doped carbon substrate and precious metals and molybdenum dispersed on the carbon substrate, wherein the molybdenum has a defect-rich state, and the molybdenum and the precious metal are dispersed on the carbon substrate in a single-atom state.
[0007] Furthermore, the noble metal is one or more of platinum, gold, palladium, iridium and rhodium, preferably platinum.
[0008] The present invention also provides a method for preparing a defect-rich molybdenum-doped fuel cell oxygen reduction catalyst, which is characterized by comprising the following steps: (1) Ultrasonic dispersion of a trace amount of noble metal salt, molybdenum source, zinc salt, terephthalic acid, and adenine in a solvent in a certain proportion, and ultrasonication for a period of time to obtain a molybdenum- and noble-doped organic framework precursor solution; (2) placing the molybdenum and noble metal doped organic framework precursor solution obtained in (1) into a reaction kettle and placing it in a heating device for hydrothermal reaction; (3) centrifuging and washing the mixed solution after the reaction in (2), and vacuum drying to obtain a powder material; (4) The powder material in step (4) is placed in the middle of a tubular furnace, an appropriate amount of ammonium salt is placed at the air inlet of the tubular furnace, and then an inert gas is introduced and calcined under an inert atmosphere to obtain a defect-rich molybdenum-doped fuel cell oxygen reduction catalyst.
[0009] Furthermore, the noble metal salt is one or more of nitrate, chloride, acetylacetonate and acetate; the molybdenum source is one or more of molybdenum hexacarbonyl, molybdenum acetylacetonate, ammonium molybdate and molybdenum chloride; the zinc salt is one or more of zinc nitrate hexahydrate and zinc acetate dihydrate; the ammonium salt is one or more of ammonium fluoride, ammonium chloride and ammonium bromide.
[0010] Furthermore, the molybdenum source is molybdenum hexacarbonyl; the noble metal salt is nitrate; and the zinc source is zinc acetate dihydrate.
[0011] Furthermore, the solvent is one or more of water, methanol, ethanol, isopropanol and N,N-dimethylformamide.
[0012] Furthermore, the ammonium salt is a mixture of ammonium chloride and ammonium bromide in a mass ratio of 1:1. The solvent further comprises a mixture of methanol, N,N-dimethylformamide and water in a volume ratio of 3:5:5.
[0013] Furthermore, the noble metal is one or more of platinum, gold, palladium, iridium and rhodium, preferably platinum.
[0014] Furthermore, the precious metal salt, molybdenum source, zinc salt, terephthalic acid, adenine and solvent, by weight, are 1 to 7 parts of precious metal salt, 1 to 7 parts of molybdenum source, 190 to 200 parts of zinc salt, 70 to 80 parts of terephthalic acid, 120 to 130 parts of adenine, and 28,000 to 30,000 parts of solvent; further preferably, the precious metal salt, molybdenum source, zinc salt, terephthalic acid, adenine and solvent, by weight, are 1 to 3 parts of precious metal salt, 1 to 3 parts of molybdenum source, 192 to 195 parts of zinc salt, 75 to 80 parts of terephthalic acid, 120 to 125 parts of adenine, and 28,500 to 29,000 parts of solvent.
[0015] Furthermore, in step (2), the hydrothermal temperature is 110-130°C, and the hydrothermal time is 48-72 hours; the vacuum drying temperature is 60-80°C, and the drying time is 15-20 hours; and the protective gas is one or more of nitrogen, helium, and argon.
[0016] Furthermore, the mass ratio of the molybdenum- and noble metal-doped organic framework precursor to the ammonium salt is 0.1-0.5, and more preferably, the mass ratio is 0.1-0.3.
[0017] The further catalyst has a half-wave potential of 0.91 V vs. RHE in 0.1 M KOH electrolyte and a half-wave potential of 0.80 V vs. RHE in 0.1 M HClO4 electrolyte.
[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) A metal organic framework is used as a carbon precursor, and a trace amount of precious metal and molybdenum are doped into it at the same time, with the content of precious metal being less than 1.0%. During the high-temperature carbonization process, an appropriate amount of ammonium salt is placed at the air inlet, and a catalyst doped with molybdenum having a high nitrogen content and rich defects is obtained by thermal decomposition of the ammonium salt. The molybdenum single atoms are evenly dispersed on the carbon substrate, fully exposing the active sites. In the prepared catalyst, the high-valence and low-ionization energy Mo regulates the d-band electronic structure of the precious metal, which is conducive to the desorption of OH-, thereby improving the kinetics of the oxygen reduction reaction; at the same time, the nitrogen content is increased and the carbon carrier is etched by thermal decomposition of the ammonium salt, which increases the number of active sites and further improves the oxygen reduction activity of the catalyst.
[0019] (2) While ensuring the catalytic effect, the loading of precious metals is as low as less than 1%, thereby reducing the production cost; the preparation method is a one-pot synthesis method with a simple process, a non-toxic and non-hazardous reaction process, and is environmentally friendly and pollution-free. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 XRD pattern of the defect-rich molybdenum-doped low-platinum catalyst prepared Figure 2 TEM image of the defect-rich molybdenum-doped low-platinum catalyst prepared Figure 3 LSV curve of the defect-rich molybdenum-doped low-platinum catalyst in 0.1M KOH electrolyte Figure 4 The LSV curve of the catalyst prepared in 0.1M KOH electrolyte for Comparative Example 1 is Figure 5 The LSV curve of the catalyst prepared in 0.1M KOH electrolyte for Comparative Example 2 is DETAILED DESCRIPTION To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be described in further detail below in conjunction with specific implementation methods and accompanying drawings, but the implementation methods of the present invention are not limited thereto.
[0021] In the present invention, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0022] Example 1 (1) Trace amounts of platinum nitrate, molybdenum hexacarbonyl, zinc acetate dihydrate, terephthalic acid, and adenine were ultrasonically dispersed in a mixed solution of methanol, N,N-dimethylformamide, and water, wherein the volume ratio of methanol, N,N-dimethylformamide, and water was 3:5:5, and the ultrasonic time was 0.5-1 h to obtain a molybdenum- and platinum-doped IISERP-MOF27 precursor solution; in parts by weight, the raw materials included 1 part of platinum nitrate, 1 part of molybdenum hexacarbonyl, 192 parts of zinc acetate dihydrate, 75 parts of terephthalic acid, 120 parts of adenine, and 28,500 parts of an organic solvent.
[0023] (2) The molybdenum and platinum doped IISERP-MOF27 precursor solution obtained in (1) was placed in a reactor and placed in a forced air drying oven for hydrothermal reaction at a temperature of 120° C. for 50 h.
[0024] (3) The precursor solution after the reaction in (2) is centrifuged and washed, and then dried in a vacuum drying oven at a temperature of 80° C. for 20 h to obtain a powdery object.
[0025] (4) The powdered material in (3) is placed in a tubular furnace, and a mixed ammonium salt of ammonium chloride and ammonium bromide in a mass ratio of 1:1 is placed at the air inlet of the tubular furnace, and calcined under a protective atmosphere at a calcination temperature of 900°C and a holding time of 2 hours to obtain a defect-rich molybdenum-doped low-platinum fuel cell oxygen reduction catalyst.
[0026] Figure 1 This is the XRD diagram of the defect-rich molybdenum-doped low-platinum catalyst. From the XRD diagram, it can be seen that the material has no obvious characteristic peaks, indicating that the material as a whole is amorphous; Figure 2This is the TEM image of the defect-rich Mo-doped low-Pt catalyst, with no obvious agglomeration of metal particles, indicating that Pt and Mo single atoms are uniformly dispersed on the carbon substrate, fully exposing the active sites.
[0027] Figure 3 This is the LSV curve of defect-rich molybdenum-doped low-platinum catalyst in 0.1M KOH electrolyte. The half-wave potential of 0.91V shows that the material has the performance of catalyzing ORR.
[0028] Embodiment 2: (1) A trace amount of palladium nitrate, molybdenum hexacarbonyl, zinc acetate dihydrate, terephthalic acid, and adenine were ultrasonically dispersed in a mixed solution of methanol, N,N-dimethylformamide, and water. The volume ratio of methanol, N,N-dimethylformamide, and water was 3:5:5. The ultrasonic time was 0.5-1 h to obtain a molybdenum- and palladium-doped IISERP-MOF27 precursor solution. In terms of weight, the raw materials included 1 part of palladium nitrate, 1 part of molybdenum hexacarbonyl, 192 parts of zinc acetate dihydrate, 75 parts of terephthalic acid, 120 parts of adenine, and 28,500 parts of an organic solvent.
[0029] (2) The molybdenum and palladium-doped MOFs precursor solution obtained in (1) was placed in a reactor and placed in a forced air drying oven for hydrothermal reaction at a hydrothermal temperature of 120° C. for 50 h.
[0030] (3) The precursor solution after the reaction in (2) is centrifuged and washed, and then dried in a vacuum drying oven at a temperature of 80° C. for 20 h to obtain a powdery object.
[0031] (4) The powdered material in (3) is placed in a tubular furnace, and a mixed ammonium salt of ammonium chloride and ammonium bromide in a mass ratio of 1:1 is placed at the air inlet of the tubular furnace, and calcined under a protective atmosphere at a calcination temperature of 900°C and a heat preservation time of 2 hours to obtain a defect-rich molybdenum-doped low-palladium fuel cell oxygen reduction catalyst.
[0032] Embodiment 3: (1) Trace amounts of iridium nitrate, molybdenum hexacarbonyl, zinc acetate dihydrate, terephthalic acid, and adenine were ultrasonically dispersed in a mixed solution of methanol, N,N-dimethylformamide, and water, wherein the volume ratio of methanol, N,N-dimethylformamide, and water was 3:5:5, and the ultrasonic time was 0.5-1 h to obtain a molybdenum- and iridium-doped IISERP-MOF27 precursor solution; by weight, the raw materials included 1 part of iridium nitrate, 1 part of molybdenum hexacarbonyl, 192 parts of zinc acetate dihydrate, 75 parts of terephthalic acid, 120 parts of adenine, and 28,500 parts of an organic solvent.
[0033] (2) The molybdenum and iridium doped MOFs precursor solution obtained in (1) was placed in a reactor and placed in a forced air drying oven for hydrothermal reaction at a hydrothermal temperature of 120° C. for 50 h.
[0034] (3) The precursor solution after the reaction in (2) is centrifuged and washed, and then dried in a vacuum drying oven at a temperature of 80° C. for 20 h to obtain a powdery object.
[0035] (4) The powdered material in (3) is placed in a tubular furnace, and a mixed ammonium salt of ammonium chloride and ammonium bromide in a mass ratio of 1:1 is placed at the air inlet of the tubular furnace, and calcined under a protective atmosphere at a calcination temperature of 900°C and a holding time of 2 hours to obtain a defect-rich molybdenum-doped low-iridium fuel cell oxygen reduction catalyst.
[0036] Comparative Example 1: (1) A trace amount of platinum nitrate, molybdenum hexacarbonyl, zinc acetate dihydrate, terephthalic acid, and adenine are ultrasonically dispersed in a mixed solution of methanol, N,N-dimethylformamide, and water, wherein the volume ratio of methanol, N,N-dimethylformamide, and water is 3:5:5, and the ultrasonic time is 0.5-1 h, to obtain a molybdenum- and platinum-doped IISERP-MOF27 precursor solution; in parts by weight, the raw materials include 1 part of platinum nitrate, 1 part of molybdenum hexacarbonyl, 192 parts of zinc acetate dihydrate, 75 parts of terephthalic acid, 120 parts of adenine, and 28500 parts of an organic solvent.
[0037] (2) The molybdenum and platinum doped IISERP-MOF27 precursor solution obtained in (1) was placed in a reactor and placed in a forced air drying oven for hydrothermal reaction at a temperature of 120° C. for 50 h.
[0038] (3) The precursor solution after the reaction in (2) is centrifuged and washed, and then dried in a vacuum drying oven at a temperature of 80° C. for 20 h to obtain a powdery object.
[0039] (5) The powdered material in (3) is placed in a tubular furnace and calcined under a protective atmosphere at a temperature of 900° C. for 2 h to obtain a molybdenum-doped low-platinum fuel cell oxygen reduction catalyst.
[0040] like Figure 4 Shown is the LSV curve of the prepared catalyst in 0.1M KOH electrolyte, with a half-wave potential of 0.766V vs.RHE.
[0041] Comparative Example 2: (1) Trace amounts of platinum nitrate, molybdenum hexacarbonyl, zinc acetate dihydrate, terephthalic acid, and adenine were ultrasonically dispersed in a mixed solution of methanol, N,N-dimethylformamide, and water, wherein the volume ratio of methanol, N,N-dimethylformamide, and water was 3:5:5, and the ultrasonic time was 0.5-1 h to obtain a molybdenum- and platinum-doped IISERP-MOF27 precursor solution; in parts by weight, the raw materials included 1 part of platinum nitrate, 1 part of molybdenum hexacarbonyl, 192 parts of zinc acetate dihydrate, 75 parts of terephthalic acid, 120 parts of adenine, and 28,500 parts of an organic solvent.
[0042] (2) The molybdenum and platinum doped IISERP-MOF27 precursor solution obtained in (1) was placed in a reactor and placed in a forced air drying oven for hydrothermal reaction at a temperature of 120° C. for 50 h.
[0043] (3) The precursor solution after the reaction in (2) is centrifuged and washed, and then dried in a vacuum drying oven at a temperature of 80° C. for 20 h to obtain a powdery object.
[0044] (4) The powdery substance in (3) is directly mixed evenly with a mixed ammonium salt of ammonium chloride and ammonium bromide in a mass ratio of 1:1, and then placed in a tubular furnace for calcination under a protective atmosphere at a calcination temperature of 900°C for a holding time of 2 hours to obtain a molybdenum-doped low-platinum fuel cell oxygen reduction catalyst.
[0045] like Figure 5 Shown is the LSV curve of the prepared catalyst in 0.1M KOH electrolyte, with a half-wave potential of 0.858V vs.RHE.
[0046] The LSV curves of the catalysts in Comparative Example 1 and Comparative Example 2 measured in 0.1M KOH electrolyte show that the half-wave potential of the catalyst material in Comparative Example 1 is significantly lower than that of the catalyst material in Example 1, indicating that the low-platinum catalyst doped with molybdenum with high nitrogen content and rich defects obtained by pyrolysis of ammonium salts can make the molybdenum atoms more evenly dispersed on the carbon substrate, fully expose the active sites, and have stronger catalytic activity. The half-wave potential of the catalyst material in Comparative Example 2 is also lower than that of the catalyst material in Example 1, but higher than that of the catalyst material in Comparative Example 1. It can be seen that placing an appropriate amount of ammonium salt at the air inlet during the high-temperature carbonization process can obtain a catalyst with better catalytic performance than directly mixing during carbonization.
[0047] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. A defect-rich molybdenum-doped fuel cell oxygen reduction catalyst, characterized in that: The catalyst comprises a nitrogen-doped carbon substrate and a noble metal and molybdenum dispersed on the carbon substrate, wherein the molybdenum and the noble metal are dispersed on the carbon substrate in a single-atom state, wherein the molybdenum has a defect-rich state.
2. The defect-rich molybdenum-doped fuel cell oxygen reduction catalyst according to claim 1, characterized in that: The noble metal is one or more of platinum, gold, palladium, iridium and rhodium, preferably platinum.
3. The method for preparing a defect-rich molybdenum-doped fuel cell oxygen reduction catalyst according to claim 1 or 2, characterized in that: The steps include: (1) Ultrasonic dispersion of a trace amount of precious metal salt, molybdenum source, zinc salt, terephthalic acid, and adenine in a solvent in a certain proportion, and ultrasonication for a period of time to obtain a molybdenum- and precious metal-doped organic framework precursor solution; (2) placing the molybdenum and noble metal doped organic framework precursor solution obtained in (1) into a reaction kettle and placing it in a heating device for hydrothermal reaction; (3) centrifuging and washing the mixed solution after the reaction in (2), and vacuum drying to obtain a powder material; (4) The powder material in step (4) is placed in the middle of a tubular furnace, an appropriate amount of ammonium salt is placed at the air inlet of the tubular furnace, and then an inert gas is introduced and calcined under an inert atmosphere to obtain a defect-rich molybdenum-doped fuel cell oxygen reduction catalyst.
4. According to the method for preparing a defect-rich molybdenum-doped fuel cell oxygen reduction catalyst according to claim 3, the precious metal salt is one or more of nitrate, chloride, acetylacetonate and acetate; the molybdenum source is one or more of hexacarbonyl molybdenum, acetylacetonate molybdenum, ammonium molybdate and molybdenum chloride; the zinc salt is one or more of zinc nitrate hexahydrate and zinc acetate dihydrate; the ammonium salt is one or more of ammonium fluoride, ammonium chloride and ammonium bromide; preferably, the molybdenum source is hexacarbonyl molybdenum; the precious metal salt is nitrate; and the zinc source is zinc acetate dihydrate.
5. According to the method for preparing a defect-rich molybdenum-doped fuel cell oxygen reduction catalyst according to claim 3, the solvent is one or more of water, methanol, ethanol, isopropanol and N,N-dimethylformamide, and preferably the solvent is a mixture of methanol, N,N-dimethylformamide and water, and the volume ratio of methanol, N,N-dimethylformamide and water is 3:5:
5.
6. According to the method for preparing the defect-rich molybdenum-doped fuel cell oxygen reduction catalyst of claim 3, the ammonium salt is a mixture of ammonium chloride and ammonium bromide, and the mass ratio of ammonium chloride to ammonium bromide is 1:
1.
7. The method for preparing a defect-rich molybdenum-doped fuel cell oxygen reduction catalyst according to claim 4, wherein the noble metal is one or more of platinum, gold, palladium, iridium, and rhodium, preferably platinum.
8. According to the method for preparing a defect-rich platinum-doped fuel cell oxygen reduction catalyst according to claim 1, the precious metal salt, molybdenum source, zinc salt, terephthalic acid, adenine and solvent are, by weight, 1 to 7 parts of precious metal salt, 1 to 7 parts of molybdenum source, 190 to 200 parts of zinc salt, 70 to 80 parts of terephthalic acid, 120 to 130 parts of adenine, and 28,000 to 30,000 parts of solvent; further preferably, the precious metal salt, molybdenum source, zinc salt, terephthalic acid, adenine and solvent are, by weight, 1 to 3 parts of precious metal salt, 1 to 3 parts of molybdenum source, 192 to 195 parts of zinc salt, 75 to 80 parts of terephthalic acid, 120 to 125 parts of adenine, and 28,500 to 29,000 parts of solvent.
9. The method for preparing a defect-rich molybdenum-doped fuel cell oxygen reduction catalyst according to claim 3, wherein the hydrothermal temperature in step (2) is 110-130° C., and the hydrothermal time is 48-72 h; the vacuum drying temperature is 60-80° C., and the drying time is 15-20 h; and the protective gas is one or more of nitrogen, helium, and argon.
10. According to the method for preparing a defect-rich molybdenum-doped fuel cell oxygen reduction catalyst according to claim 3, the mass ratio of the molybdenum- and noble metal-doped organic framework precursor to the ammonium salt is 0.1-0.5, and more preferably, the mass ratio is 0.1-0.3.
Citation Information
Cited By
High-durability Pt fuel cell cathode catalyst and preparation method thereof
CN120809848A
